IMPLEMENTATION OF THE REGENT REGULATION OF EAST OGAN KOMERING ULU NUMBER 20 OF 2021 CONCERNING GUIDELINES FOR SOCIAL ASSISTANCE FOR THE POOR IN THE REGENCY OF EAST OGAN KOMERING ULU - Puspa Rini Anggraini; Ardiyan Saptawan; Raniasa Putra (RADJA PUBLIKA, 2026)
This study aims to analyze the implementation of East OKU Regent Regulation Number 20 of 2021 concerning grief social assistance in East OKU Regency by assessing the effectiveness of policy implementation at the local government level. The study used a descriptive qualitative method through in-depth interviews, field observations, and documentation studies of policy implementers and beneficiaries. The analytical framework refers to George C. Edward III's policy implementation theory, which emphasizes four main variables: communication, resources, disposition, and bureaucratic structure. The results indicate that policy implementation has not been optimal due to obstacles in each implementation variable. The communication aspect still faces obstacles such as a lack of policy socialization, uneven information distribution, and ineffective inter-agency coordination. In terms of resources, limited budget, staff numbers, and technical competencies affect the speed of service. The disposition variable shows differences in commitment, understanding, and attitudes of implementers towards program objectives. Meanwhile, a rigid, procedural, and centralized bureaucratic structure causes slow administrative processes and is less responsive to community needs. Overall, these factors contribute to delays in the distribution of grief social assistance and reduce beneficiary satisfaction levels. This study recommends improving coordination, strengthening human resource capacity, simplifying bureaucratic procedures, and optimizing service information systems to ensure more effective, transparent, and accountable policy implementation. Furthermore, regular data-driven evaluations, consistent internal oversight, and the involvement of communities and local stakeholders in program planning and monitoring processes are needed to ensure policy sustainability, increase public trust, and strengthen the accountability and quality of local government social services. Cross-sectoral collaborative efforts also need to be continuously enhanced.